The association of coronary artery calcium score with glomerular filtration rate and the influence of sex, age, blood pressure, and cholesterol - Bosdriesz, J. R.; Semenov, V. V.; Kuryata, O. V. (Medicni Perspektivi, 2020)
Chronic kidney disease puts an individual at a higher risk of all-cause and cardiovascular death. Coronary artery calcium score reflects the accumulation of calcium in the walls of the coronary arteries and a higher coronary artery calcium score is associated with lower survival rates. It is unclear if control of conventional risk factors is enough to reduce cardiovascular risk in patients with chronic kidney disease. The aim of this study was to investigate if the association between estimated glomerular filtration rate and coronary artery calcium score in the Ukrainian population differs by sex, age, blood pressure, and total cholesterol.This cross-sectional study was conducted on a sample of patients who underwent measurement of coronary artery calcium score at Dnipropetrovsk Mechnikov Regional Hospital, Dnipro, Ukraine. Inclusion criteria: age >40 years old, available data about coronary artery calcium score and estimated glomerular filtration rate. Exclusion criteria: the presence of known cardiovascular disease, diagnosis of diabetes mellitus, estimated glomerular filtration rate <30 ml/min and extreme coronary artery calcification (coronary artery calcium score >1500 Agatston units). 137 patients (54 males and 83 females), median age 59.0 [54.0;67.0] years were enrolled in the study. In the patients with lower eGFR there was non-significantly higher coronary artery calcium score (p=0.07). In males with eGFR ≥90 ml/min, 60-89 ml/min, and 30-59 ml/min coronary artery calcium score didn’t differ significantly, while in females a lower estimated glomerular filtration rate was associated with a higher coronary artery calcium score. A lower estimated glomerular filtration rate was significantly associated with a higher coronary artery calcium score in the patients with systolic blood pressure ≥140 mmHg (p=0.04), but not in patients with diastolic blood pressure ≥90 mmHg. In the patients with total cholesterol <5.0 mmol/l and ≥5.0 mmol/l coronary artery calcium score tended to be higher in the patients with lower estimated glomerular filtration rate. A lower estimated glomerular filtration rate in our study was associated with a higher coronary artery calcium score in females, patients aged ≥55 years old and in patients with systolic blood pressure ≥140 mmHg.